Tubulin polyglutamylation differentially regulates microtubule‐interacting proteins. (13th January 2023) - Genova, Mariya; Grycova, Lenka; Puttrich, Verena; Magiera, Maria M; Lansky, Zdenek; Janke, Carsten; Braun, Marcus
Abstract: Tubulin posttranslational modifications have been predicted to control cytoskeletal functions by coordinating the molecular interactions between microtubules and their associating proteins. A prominent tubulin modification in neurons is polyglutamylation, the deregulation of which causes neurodegeneration. Yet, the underlying molecular mechanisms have remained elusive. Here, using in‐vitro reconstitution, we determine how polyglutamylation generated by the two predominant neuronal polyglutamylases, TTLL1 and TTLL7, specifically modulates the activities of three major microtubule interactors: the microtubule‐associated protein Tau, the microtubule‐severing enzyme katanin and the molecular motor kinesin‐1. We demonstrate that the unique modification patterns generated by TTLL1 and TTLL7 differentially impact those three effector proteins, thus allowing for their selective regulation. Given that our experiments were performed with brain tubulin from mouse models in which physiological levels and patterns of polyglutamylation were altered by the genetic knockout of the main modifying enzymes, our quantitative measurements provide direct mechanistic insight into how polyglutamylation could selectively control microtubule interactions in neurons. Synopsis: Posttranslational modifications of tubulin are expected to control the functions of a wide range of microtubule‐interacting proteins. Here, in vitro reconstitution assays with purified brain tubulin from mouse models lacking specific tubulin‐modifying enzymes show that tubulin modification patterns selectively impact microtubule‐protein interactions. The binding of the Alzheimer's disease‐associated protein Tau to microtubules is enhanced by tubulin polyglutamylation on both α‐ and β‐tubulin. The microtubule‐severing activity of katanin is increased on polyglutamylated microtubules, with no preference for α‐ or β‐tubulin polyglutamylation. The processivity of the kinesin‐1 motor Kif5B is specifically controlled by β‐tubulin polyglutamylation, while insensitive to the modification status of α‐tubulin. Abstract : In vitro assays with purified tubulin from mice lacking tubulin‐modifying enzymes show that physiologically relevant tubulin modification patterns selectively impact microtubule‐protein interactions.